Photocatalytic activity of Ag-N co-doped ZnO nanorods under visible and solar light irradiations for MB degradation. (December 2016) - Welderfael, Tesfay; Pattabi, Manjunatha; Pattabi, Rani M.; G, Arun Kumar Thilipan
Abstract: Zinc oxide nanorods (CZ), silver-doped zinc oxide nanorods (CAZ), nitrogen-doped zinc oxide nanorods (CNZ), and silver-nitrogen co-doped zinc oxide nanorods(CANZ) were synthesized using the chemical precipitation method. The as-synthesized nanorods were characterized using x-ray diffraction (XRD); scanning electron microscopy (SEM), and UV–vis spectroscopy (UV–vis). The photocatalytic degradation of methylene blue (MB) was studied using the as-synthesized nanorods under both solar and visible light irradiations. CANZ has the highest photocatalytic activity under both visible as well as solar light irradiations; with CNZ, CAZ and CZ show a decreasing order in their photocatalytic activities. In addition to this, the photocatalytic activity of the as-synthesized nanorods was compared under both light sources. The photocatalytic activity of all the nanorods is higher under solar light as compared to the visible light irradiation. Therefore, sun light is the best light source for the removal of dyes from the environment.